The defences of Macau - Garrett, Richard J. (Hong Kong University Press, 2010)
This text fills the gap in describing Macau's defensive works and weapons, on land and sea, much of which has been previously unrecorded. These defenses were crucial to the survival of Portuguese Macau and the book covers the period from its founding in 1557 until the late 20th century.